2010
DOI: 10.4028/www.scientific.net/amr.95.85
|View full text |Cite
|
Sign up to set email alerts
|

Polyurea – The New Generation of Lining and Coating

Abstract: Few seconds setting time, superior flexibility along with high mechanical strength and moisture insensitivity are only a small portion of the characteristics of the unique technology named Polyurea. This technology is on the move around the globe and recently some intriguing projects were done also in Israel. This paper is a brief introduction of the Polyurea technology. Nearly two decades ago, a new technology was introduced to the world. It was not an innovative semi-flexible Epoxy, with a better UV stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Polyurea linings are structurally divided into aromatic and aliphatic categories; aromatic polyurea has low resistance against the UV rays. It loses its color and gloss; therefore, it is not suitable for application in the outdoors and beauty purposes and is mostly used indoor buildings while the aliphatic type is resistant against the UV rays and is used as a complete coating; of course, it should be considered that the latter is much more expensive than the former 35 …”
Section: Polyurea Coatings and Liningsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyurea linings are structurally divided into aromatic and aliphatic categories; aromatic polyurea has low resistance against the UV rays. It loses its color and gloss; therefore, it is not suitable for application in the outdoors and beauty purposes and is mostly used indoor buildings while the aliphatic type is resistant against the UV rays and is used as a complete coating; of course, it should be considered that the latter is much more expensive than the former 35 …”
Section: Polyurea Coatings and Liningsmentioning
confidence: 99%
“…The advancement and versatility of the applications, including high moisture tolerance—whether in terms of environment, substrate, or temperature—have been making polyurea a very suitable coating for the concrete in the construction applications such as roof repair, retaining liners (due to high abrasion resistance), membranes, parking decks, bridges, and coastal sectors 21 . It has been shown that these coatings in the concrete reduce the water absorption and improve the chemical abrasion and resistance against the cold 35 …”
Section: Polyurea Coatings and Liningsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional polymeric coatings have always been widely used in the construction sector. The main categories of polymeric coatings are epoxy resins [18][19][20], acrylics [21][22][23] and polyurethanes [24][25][26], each of them with their own strengths and weaknesses as reported in Table 1. They exert their protective ability by increasing the resistance against aqueous solutions penetration due to a barrier effect.…”
Section: Available Surface Treatmentsmentioning
confidence: 99%
“…Polyurethane-polyurea hybrid technology represents a major type of resins in development of the coating for different substrates including metal, concrete, wood and asphalt [1,2]. This technology is based on preparation of polyurea based on the reaction of polyurethane prepolymer with a resin blend [3][4][5][6][7]. The resin blend mad up of amine terminated polymer resin or an amine chain extender.…”
Section: Introductionmentioning
confidence: 99%